2010
DOI: 10.1590/s0074-02762010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Antibody reactivity against potato apyrase, a protein that shares epitopes with Schistosoma mansoni ATP diphosphohydrolase isoforms, in acute and chronically infected mice, after chemotherapy and reinfection

Abstract: Apyrase and experimental schistosomiasis • P Faria-Pinto et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Potato apyrase, synthetic peptide, SEA and soluble worm antigen preparation (SWAP) -Potato apyrase was purified from a commercial strain of Solanum tuberosum and used to obtain polyclonal antiserum in a New Zealand White rabbit or BALB/c mice, as earlier described (FariaPinto et al 2004, 2010b, Kettlun et al 2005. A peptide (SmB2LJ; r175-194; AALSLTKLINIAETSLPVDV) belonging to a conserved domain from soluble S. mansoni SmATPDase 2 (GenBank accession ABI79456.1) was designed based on a strategic comparative study with its potato apyrase counterpart (r97-116; AANSLEPLLDGAE-GVVPQEL; 40% identity and 65% similarity over 20 amino acids) (GenBank accession P80595), which maintained the predicted epitopes available for antibody binding (Faria-Pinto et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Potato apyrase, synthetic peptide, SEA and soluble worm antigen preparation (SWAP) -Potato apyrase was purified from a commercial strain of Solanum tuberosum and used to obtain polyclonal antiserum in a New Zealand White rabbit or BALB/c mice, as earlier described (FariaPinto et al 2004, 2010b, Kettlun et al 2005. A peptide (SmB2LJ; r175-194; AALSLTKLINIAETSLPVDV) belonging to a conserved domain from soluble S. mansoni SmATPDase 2 (GenBank accession ABI79456.1) was designed based on a strategic comparative study with its potato apyrase counterpart (r97-116; AANSLEPLLDGAE-GVVPQEL; 40% identity and 65% similarity over 20 amino acids) (GenBank accession P80595), which maintained the predicted epitopes available for antibody binding (Faria-Pinto et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Sm ATPDase 1 is located on the surface and Sm ATPDase 2 is in the tegument and secreted by eggs and adult worms ( Faria-Pinto et al., 2004 ; Fietto et al., 2004 ; Levano-Garcia et al., 2007 ). Both isoforms showed immune cross-reactivity with antipotato apyrase antibodies ( Faria-Pinto et al., 2008 ; Faria-Pinto et al., 2010 ). Macrophages incubated with antibodies against the ATPDase isoforms of S. mansoni showed reduced NTPDase 1 activity, and the parasite proliferation was inhibited ( Marconato et al., 2017 ).…”
Section: Development Of E-ntpdases Inhibitorsmentioning
confidence: 99%
“…4,9,10 Previously, our group showed that SmATPDases 1 and 2 isoforms are antigenic and have cross-reactivity with antipotato apyrase antibodies. 4,[11][12][13] Furthermore, the alignment of the primary sequence of NTPDase of many organisms shows shared domains, 14 encouraging studies comparing the isoforms present in the parasite with the protein expressed in the mammalian host.…”
Section: Introductionmentioning
confidence: 99%